2022
DOI: 10.3390/pathogens12010060
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Red Fox (Vulpes vulpes) Demographics to Monitor Wildlife Diseases: A Spotlight on Echinococcus multilocularis

Abstract: The assessment of red fox population density is considered relevant to the surveillance of zoonotic agents vectored by this species. However, density is difficult to estimate reliably, since the ecological plasticity and elusive behavior of this carnivore hinder classic methods of inference. In this study, red fox population density was estimated using a non-invasive molecular spatial capture-recapture (SCR) approach in two study areas: one in a known hotspot of the zoonotic cestode Echinococcus multilocularis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 75 publications
(101 reference statements)
0
6
0
Order By: Relevance
“…They found that definitive host species richness showed a negative relationship with E. multilocularis suitability and that the proportion of definitive hosts in the community of carnivores was positively related with E. multilocularis suitability ( Botero-Cañola et al, 2019 ). Finally, the feeding behaviour of definitive hosts might mediate the effect of their density on parasite transmission, as a reduction of feeding on non-competent hosts when alternative resources are available might explain why in some instances the density of definitive hosts is negatively related to parasite transmission ( Celva et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…They found that definitive host species richness showed a negative relationship with E. multilocularis suitability and that the proportion of definitive hosts in the community of carnivores was positively related with E. multilocularis suitability ( Botero-Cañola et al, 2019 ). Finally, the feeding behaviour of definitive hosts might mediate the effect of their density on parasite transmission, as a reduction of feeding on non-competent hosts when alternative resources are available might explain why in some instances the density of definitive hosts is negatively related to parasite transmission ( Celva et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Neither types of hosts have direct data on population size within the study area. In the case of carnivores, hunting bag data can be used as an indicator of trends in population change 34 36 . The data collected in a national database show an explicit increase during the previous decade (Supplementary Table S1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The loss of landscape heterogeneity resulted in vole dominance both in the habitat and in the pellets 42 . In the Alps, an opposite phenomenon is observed as habitat fragmentation enhances the population expansion of Alpine rodent species resulting in exacerbation of E. multilocularis epizootic 34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Europe, the historical endemic areas are Austria, France, Germany, and Switzerland, and that range has expanded to include Eastern and Northern Europe ( 3 ). In Italy, infected foxes have been reported over the past 20 years in the Trentino-Alto Adige region ( 4 7 ). Autochthonous animal transmission might occur in the area ( 8 ), and prevalence in foxes seems to be increasing ( 9 ).…”
mentioning
confidence: 99%